Personality disorders, addictions and psychopathy as predictors of criminal behaviour in a prison sample - G Flórez; V Ferrer; LS García; MR Crespo; M Pérez; PA Saiz (Sociedad Española de Sanidad Penitenciaria, 2019)
Abstract Aims Disturbances in personality and addictions are associated with an increased risk of committing crimes and therefore of being imprisoned. In this study, the relationship between these factors is analyzed through a sample of inmates in the Prison of Pereiro de Aguiar, Ourense. Material and method 204 inmates participated in this transversal simple blind design study. The following variables were analyzed: presence of personality disorders and psychopathy, history of addictive psychoactive substance use, criminal history and socio-demographic variables. Results 101 (49.5%) inmates received a diagnosis of personality disorder, the most frequent being: narcissistic, 43 (21.08%); antisocial, 38 (18.63%); and paranoid, 29 (14.22%). The presence of any personality disorder was associated with an increase in the risk of committing crimes, especially violence and crimes against property. The most frequent personality disorders were associated with higher scores in the psychopathy assessment tools. Higher scores in the Psychopathy Checklist Reviewed (PCL-R) correlated with an increased risk of committing the following crimes: violent, against public health, against property and disorderly conduct. The consumption of addictive psychoactive substances was associated with the commission of crimes against property. Methadone stood out for its protective role against the commission of violent crimes. Discussion This sample shows that inmates have a higher prevalence of personality disorders, psychopathy and consumption of addictive psychoactive substances. These three variables significantly increased the risk of committing crimes.